Analisis Komitmen Organisasi, Disiplin Kerja & Lingkungan Kerja Terhadap Kinerja Pegawai di Masa Pandemi Covid-19 - Ahmadi Ahmadi; Toto Hardiyanto (Journal of Applied Management Research, 2021)
The cutting and postponement of Regional Performance Allowances during the Covid-19 pandemic had an impact on the performance of Civil Servants. This study aims to analyze the effect of organizational commitment, work discipline and work environment on performance and formulate strategies to improve performance during the Covid-19 pandemic by taking a case study at the Central Jakarta City Fire and Rescue Agency. This study uses a quantitative approach with data collection techniques through surveys, by distributing questionnaires to 56 respondents with sample criteria through non-probability sampling techniques. The results showed that the three independent variables had a significant influence on the dependent variable and the preferred strategy was the "Defensive" Strategy (WT). It can be concluded that the three independent variables have an effect either partially or simultaneously on the dependent variable and strategies aimed at reducing internal weaknesses and avoiding external threats are very appropriate to use during a pandemic. The policy for changing the Standard Operational Procedure (SOP), the supervision of the Occupational Health and Safety Management System (SMK3) must be carried out immediately by the organization.